Influence of lateral injection from the circular strut on mixing performance of hydrogen jet at supersonic combustion chamber. (January 2023) - Li, Z.; Leng, Jiaxuan; Abu-Hamdeh, Nidal H.; Daqrouq, Khaled O.; Musa, Awad; Nusier, Osama K.
Abstract: An efficient injection system is essential for the advance of the scramjet engine for high-speed flight. In present study, the effects of lateral injection from the circular strut on the fuel mixing and distributions are comprehensively investigated. In this study, computational technique of CFD is used for the visualization of fuel mixing mechanism in real 3-D domain. The effects of strut height on circulation factor and mixing zone are also investigated. The variations of Mach contour and streamline under the effects of strut height are compared. Presented results show that the circulation factors are reduced when single cross jet is replaced by the lateral injection system. Comparison of mixing shows that mixing performance of improves about 26% when strut height of lateral injection is increased from 2 mm to 4 mm. Besides, replacement of the single normal injection with lateral nozzle located on circular strut improves mixing performance about 41% and 71% behind the injector.